A Monitoring System of Battery LiFePO4 for Assessment Stand-Alone Street Light Photovoltaic System Based on LabVIEW Interface for Arduino - Anif Jamaluddin; Anafi Nur’aini; Arif Jumari; Agus Purwanto (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The paper presents monitoring and assessment system of battery LiFePO4 performance that applied on a stand-alone photovoltaic system. A stand-alone photovoltaic system is constructed by photovoltaic module 50 Watt Peak, Pulse Width Modulation solar controller, battery module LiFePO4 battery (12 Volt 21 Ah), and street light 10 watt. To overcome the data acquisition, a simple monitoring system has been designed using LabVIEW Interface for Arduino. The voltage divider, current sensing type ACS712, temperature and humidity sensor, and light intensity sensor were used to collect the data. The data processed by a dual microcontroller (ATmega-2560 and ATmega-328) and LabVIEW software on Personal Computer. The assessment of stand-alone photovoltaic system includes battery LiFePO4 performance (State of Charge, voltage, and current) during charging and discharge condition, the power efficiency, and environmental condition (temperature, humidity and solar radiation). In the discharge condition, voltage battery and State of Charge decreased about 40% after 12 hours operated. In the charge condition, the current battery fluctuated in the range of 0.10 A-1.95 A and the State of Charge increased up to 25% after 8 hours operated. It indicates that the power of the battery has always lacked.